2000
DOI: 10.1063/1.1311593
|View full text |Cite
|
Sign up to set email alerts
|

An extended Maxwell–Wagner theory for the electric birefringence of charged colloids

Abstract: Recent frequency resolved electric birefringence experiments on dilute suspensions of charged, ellipsoidal particles reveal new relaxation features in the MHz frequency range. Such behavior can be explained in terms of surface transport processes. Here we develop a model for the electric polarizability of spheroidal particles by combining features of electrokinetic and Maxwell–Wagner theories. The model accurately depicts the high frequency features and relates them to the colloidal properties of the polyelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 15 publications
8
79
0
Order By: Relevance
“…O'Konski 18 found that the presence of a conducting shell (like the double layer surrounding a nonconducting particle) can be taken into account by assigning a certain bulk conductivity to the particle's material. Because this is often the case, 7,19 the relaxation is usually called Maxwell-Wagner-O'Konski (MWO) relaxation. It has been shown that in colloids the electrokinetic features of the polarizability can be included using an asymptotic theory that employs an appropiate surface conductivity.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Konski 18 found that the presence of a conducting shell (like the double layer surrounding a nonconducting particle) can be taken into account by assigning a certain bulk conductivity to the particle's material. Because this is often the case, 7,19 the relaxation is usually called Maxwell-Wagner-O'Konski (MWO) relaxation. It has been shown that in colloids the electrokinetic features of the polarizability can be included using an asymptotic theory that employs an appropiate surface conductivity.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…It has been shown that in colloids the electrokinetic features of the polarizability can be included using an asymptotic theory that employs an appropiate surface conductivity. Thus, at high ionic strengths, high potentials, and high frequencies, 19 the conduction processes on the particle surface can be considered by means of an equivalent particle surface conductivity, K σ , that can be expressed in terms of the -potential, . Hence, the application of Maxwell-Wagner-O'Konski formula to colloids is usually called extended Maxwell Wagner model.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…[27][28][29] If these are not spherical, their electric polarizability is anisotropic, 5,11,13,30 and for axially symmetric particles, this anisotropy can be expressed by the scalar quantity ∆α e = α e b −α e a , being α e b (α e a ) the electric polarizability along their major(minor) axis, b and a, respectively. In general, this quantity is different from zero, and hence, the total dipole moment induced by an applied field is not parallel to the latter.…”
Section: Electro-orientation Of Non-spherical Particlesmentioning
confidence: 99%
“…Electric Birefringence Spectroscopy (EBS), the analysis of the behaviour of the birefringence as a function of the frequency of the applied field, albeit yet incomplete, can provide exhaustive information about the different polarization mechanisms of the nanoparticles and their electric double layers (EDLs). 2,5,6,[10][11][12][13] However, although the foundations of the electric birefringence have been long-established, the process is hitherto not understood on the whole and cannot yet be considered as a widespread characterization technique. 12,[14][15][16] Thus, microscopic models relating the nanoparticle properties to their macroscopic birefringent response are to date not completely satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…O'Konski proposed a surface conductance term to account for the effect of electric double layer [87], and the same mechanism was also extended to the study of ellipsoidal colloids [88]. The Maxwell-Wagner-O'Konski theory has a simple analytic formulation which gives qualitatively correct predictions, but it suffers from one main drawback: Since the theory is entirely formulated in terms of macroscopic properties, such as the conductivities and permittivities, the polarization charges are taken to be localized at the particle/medium interface, and their spatial distribution is entirely neglected.…”
Section: Maxwell-wagner Theory and Electrokinetic Theorymentioning
confidence: 99%